Pemetaan Restoran Jepang dan Kuliner Milenial di Surabaya - Amalijah, Eva; Fredy, Mochammad (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
The food that a person consumes has an influence in determining identity, existence, and legitimacy. As something that is important and influential for humans, food generally has characteristics to distinguish it from other foods. In this context, Japan has uniquely Japanese food that distinguishes it from food from other countries. Therefore, Japan as one of the countries that utilizes popular culture as its export commodity uses food as a tool of cultural diplomacy. This study examines the relationship between culinary choices among millennials and gender at Japanese restaurants in Surabaya. Through an interpretative quantitative method of studying Japanese culinary culture, the data will be mapped, interpreted, and then studied in depth the relationship between culinary choices among millennials and gender in Japanese restaurants in Surabaya. The results of the study read with the concepts of Japanese pop culture, especially about shoku bunka (culinary culture) and gender. So that the output is in the form of knowledge about the existence of gender that enters the realm of food and influences the choices of young millennials in determining the food menu at Japanese restaurants in the city of Surabaya.